Mechanisms of Signaling through Urokinase Receptor and the Cellular Response - Koshelnick, Yuri; Ehart, Monika; Stockinger, Hannes; Binder, Bernd R. (Thrombosis and Haemostasis, 1999)
The urokinase-urokinase receptor (u-PA-u-PAR) system seems to play a crucial role in a number of biological processes, including local fibrinolysis, tumor invasion, angiogenesis, neointima and atherosclerotic plaque formation, inflammation, and matrix remodeling during wound healing and development.1-6 Binding of urokinase to its specific receptor provides cells with a localized proteolytic potential. It stimulates conversion of cell surface-bound plasminogen into active plasmin, which, in turn, is required for proteolytic degradation of basement membrane components, including fibronectin, collagen, laminin, and proteoglycan core proteins.7 Moreover, plasmin activates other matrix-degrading enzymes, such as matrix metalloproteinases.8 Overexpression of u-PA/u-PAR correlates with tumor invasion and metastasis formation,9-13 while reduction of cell-surface bound u-PA and inhibition of u-PAR expression leads to a significant decrease of invasive and metastatic activity.14 Specific antagonists that suppress binding of u-PA to u-PAR have been shown to inhibit cell-surface plasminogen activation, tumor growth, and angiogenesis both in vitro and in vivo models.15,16Independently of its proteolytic activity, u-PA is implicated in many biological processes that seem to require u-PAR-mediated intracellular signal transduction, such as proliferation, chemotactic movement and adhesion, migration, and differentiation.17 Data obtained in the late 1980s indicated that u-PA not only provides cells with local proteolytic activity, but might also be capable of transducing signals to the cell.18-22 At that time, however, the u-PAR has just been isolated, cloned, and identified as a glycosylphosphatidylinositol (GPI)-linked protein and not a transmembrane protein. Signaling via the u-PAR was, therefore, regarded as being unlikely, and the effects of u-PA on cell proliferation18-22 were thought to be mediated by proteolytic activation of latent growth factors. The assumption of direct signaling via u-PAR was, in fact, considered controversial, until about 10 years later when a physical association between u-PAR and signaling proteins was found.23 From this report on, several proteins associated with u-PAR have been identified. Now, u-PAR seems to be part of a large “signalosome” associated and interacting with several proteins on both the outside and inside of the cell.